The path of economics research production: Insights into the seesaw between theory and empirics - Jo\~ao Ricardo Faria; Rajeev K. Goel; Neela D. Manage (Kiel Institute for the World Economy (IfW Kiel), 2023)
This paper provides insights into the apparent seesaw between the generation of theoretical versus empirical economics research over time. A dynamic model considers the incentives of researchers to focus on empirical versus theoretical papers. It yields the main characteristics of the path-changing of economics research, from theoretical-intensive to empirical-focused. The model has two equilibria, one with a higher proportion of theoretical papers and another with a higher proportion of empirical papers. Curiously, the equilibrium with greater theoretical papers is stable, while the one with more empirical papers is a saddle point. This suggests that the current trend of increasing empirical research is unlikely to last.
Keywords: A11; A19; 330; economic research; theory; empirics; publications; journals